Weaning Practices Impact Factors and Outcomes: Cross-Sectional Study - Al Harthi, Hasina; Al Jufaili, Fathiya; Al Ubaidani, Salwa Ali; Al Awaidy, Salah T. (International Journal of Innovative Research in Medical Science, 2022)
Objective: Numerous policies and initiatives have been set up in hospitals and health centers supported by the Ministry of Health (MOH) in Oman, to comply with international guidelines on breastfeeding and supplementary breastfeeding of infants and children. Highlight maternal practices in breastfeeding and weaning will exemplify the gap between maternal knowledge and real practice. The objective of the study was to explore the practices related to weaning and its relation to child weight and hemoglobin level. Methods: The study used a cross-sectional design between September 2018 and February 2019. Pretested form used to collect data from mothers of 9 to 13-month-old children attending an immunization clinic. Collected data included; demographic data, breastfeeding history, and complementary feeding practices. Anthropometric measurement and blood sampling for hemoglobin (Hb) levels. Results: A total of 181 children was enrolled. Exclusive breastfeeding for six months was reported in 9.9% (n=18) of the sample. The majority of mothers started with starch/cereal 48.1% (n=87) as their first supplementary diet. However, we found that 28.2% (n=51) began using commercial foods. Moreover, 21.7% (n=39) provided commercial food as a main daily snack. The daily food group was composed of 58% cereal (n=105). Blood was collected on 87.8% (n=159) of the children for a Hb concentration test. The mean Hb level found was 10.8 (SD: 0.99). Protein consumption was not significantly related to the Hb level (p = 0.26). However, it was related to the nutritional status of the child (p=0.013), with all children whose waste did not consume a protein source most of the time. Conclusions: While the MOH efforts are well documented, there are still areas where community enforcement is inadequate. Findings: The employment of mothers had a significant influence on the duration of exclusive breastfeeding, and the nutritional status of infants and infants was highly dependent on protein intake in the diet. Efforts should be made to identify knowledge gaps, and barriers faced by mothers.